Impact of environmental factors on millet quality in the eastern and western regions on the Lyuliang Mountains (Bangladesh Journal of Botany, 2025)
This study aims to examine the influence of three categories of  environmental factors-climatic, soil and topographic  conditions, on millet quality in the eastern and western regions of the Lyuliang Mountains. Ten millet varieties were assessed across 15 quality indices, including protein, fat, and essential amino acids, at five locations on the eastern and western slopes of the Lyuliang Mountains. Comprehensive environmental data related to each sample site were collected. Principal component analysis (PCA) and correlation analysis were employed to explore the relationships between ecological factors and the nutritional composition of the millet. The results showed that certain nutrients in the millet were significantly correlated with specific environmental factors. Millet from Xingxian County exhibited the highest quality, with nutrient composition variation remaining below 10%. Environmental factors played a more substantial role in determining millet quality than genetic varieties. Average daily temperature showed a significant negative correlation (P